2009
DOI: 10.1002/ca.20778
|View full text |Cite
|
Sign up to set email alerts
|

The “safe zone” in medial percutaneous calcaneal pin placement

Abstract: Percutaneous pin insertion into the medial calcaneus places a number of structures at risk. Evidence suggests that the greatest risk is to the medial calcaneal nerve (MCN). The medial calcaneal region of 24 cadavers was dissected to determine the major structures at risk. By using four palpable anatomical landmarks, the inferior tip of the medial malleolus (point A), the posterior superior portion of the calcaneal tuberosity (point B), the navicular tuberosity (point C), and the medial process of the calcaneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…8 In calcaneal surgery, the most common injury appears to be sensory nerve damage. 26 Neurovascular injury is an iatrogenic injury that is rarely seen postoperatively, and a definite incidence rate has not been reported. In the 21 papers included here, we calculated the incidence rate to be 2.8%.…”
Section: Discussionmentioning
confidence: 99%
“…8 In calcaneal surgery, the most common injury appears to be sensory nerve damage. 26 Neurovascular injury is an iatrogenic injury that is rarely seen postoperatively, and a definite incidence rate has not been reported. In the 21 papers included here, we calculated the incidence rate to be 2.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Slight plantar flexion was noted in the cadaveric feet due to fixation methods but it has been shown that there is only a weak correlation between the degree of flexion and difference in measurement distances 17 . Our specimens had no trauma to the calcaneus and thereby exhibited normal calcaneal anatomy without fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have attempted to divide the surfaces of the calcaneus into zones according to increasing risk of injury to neurovascular and tendinous structures [16][17][18][19][20] but have yet to come to a clear agreement. It has been suggested by Labronici et al that vascular structures found superficially to the anteromedial surface of the calcaneus are at high risk of damage during wire fixation performed via the lateral aspect of the hindfoot 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have attempted to define an anatomical safety zone for placing external fixators and traction pins in the medial region of the calcaneus (7)(8)(9)(10) . The distances of placement sites from tendons and neurovascular structures in various anatomical regions have been used as a method for describing the safety zone in a small number of cadaveric studies (7,8,10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…The distances of placement sites from tendons and neurovascular structures in various anatomical regions have been used as a method for describing the safety zone in a small number of cadaveric studies (7,8,10,11) . However, these studies present limitations through ignoring variations in the tibial nerve, with its medial, lateral and calcaneal branches, because of the absence of research in the areas at risk or through creation of complex methods that become difficult to use in clinical practice (7,8,11) .…”
Section: Discussionmentioning
confidence: 99%